Exploring the synergy between emotional intelligence and self-esteem among university students in Ghana - Daniel Miezah; Maxwell Peprah Opoku; Christopher Fenu; Raphael Quainoo; Ebenezer Mensah Gyimah (BMC Psychology)
Abstract Background The need for educational institutions to create a conducive learning environment for participation of all students in school activities is one of the pillars advocated under Goal 4 of the United Nations Sustainable Development Goals. While there are structures institutionalized to promote students’ well-being, universities are faced with a myriad of challenges which can negatively impact mental health and disrupt the overall learning experiences of students. This study explored the relationship between Emotional Intelligence and Self-Esteem which have been found to influence the mental health of students. Method Informed by the cross-sectional design, one thousand and twenty (N = 1020) university students were recruited to self-report their Emotional Intelligence and Self-Esteem. The participants completed the Schutte Emotional Intelligence scale and the Rosenberg’s Self-Esteem scale. The data were validated using confirmatory factor analysis, means were computed, followed by multivariate analysis of variance and hierarchical multiple regression. Results The study showed that participants were ambivalent on both EI and self-esteem. The hypothesized relationship between Emotional Intelligence and Self-Esteem was supported by the study findings. More so, demographic variables such as gender, religion and programme of study provided further insight into Emotional Intelligence and Self-Esteem of participants. Conclusion In conclusion, the researchers of this study called on educators and university administrators to prioritize the Emotional Intelligence and Self-Esteem of students in mental health interventions. The need for partnership between administrators and religious leaders and other study implications, are discussed.